QUANTITATIVE AND QUALITATIVE INVESTIGATION OF THREE-DIMENSIONAL GAIT ANALYSIS IN PATIENTS WITH CERVICAL MYELOPATHY - Diara Raiane Santos; Emilly Zatta Pimenta; Thabata Pasquini Soeira; Felipe de Souza Serenza; Mariana Demétrio de Sousa Pontes; Carlos Fernando Pereira da Silva Herrero (Acta Ortopédica Brasileira)
ABSTRACT Objective: This study aims to describe a kinematic gait assessment protocol and identify its main alterations in individuals with cervical spondylotic myelopathy (CSM) compared to healthy patients. Methods: In total, 14 patients diagnosed with CSM were enrolled and submitted to a three-dimensional gait analysis. The movement of patients was captured with infrared emission cameras that identified tracking markers placed on the lower limbs. Reference positions were used, and the patients walked along a rubberized walkway. The Gait Profile Score (GPS) and Movement Analysis Profile (MAP) were used to analyze variables. Results were subjected to a Student’s t-test at 95% confidence interval. The R Core Team (2016) software was used for statistical analysis, graphically comparing the study results with data from healthy patients. Results: When comparing the kinematic data bilaterally, no statistical differences were found. However, graphical analysis showed changes in the gait of patients with CSM compared to healthy individuals. There were differences in all movements, with a more significant discrepancy in hip and knee flexion and extension, dorsiflexion and plantar flexion, and internal and external hip rotation. Conclusion: We describe a protocol for gait kinematics assessment using GPS and MAP, and we presented the differences in gait kinematics in patients with CSM compared to healthy individuals. Level of Evidence II, Prospective study.